Three-dimensional strain localization of water-saturated clay and numerical simulation using an elasto-viscoplastic model - Higo, Y.; Oka, F.; Kodaka, T.; Kimoto, S. (Philosophical magazine (Abingdon, England), 2006)
Since strain localization is a precursor of failure, it is an important subject to address in the field of geomechanics. Strain localization has been analysed for geomaterials by several researchers. Many of the studies, however, treated the problems brought about by strain localization as two-dimensional problems, although the phenomena are generally three-dimensional. In the present study, undrained triaxial compression tests using rectangular specimens and their numerical simulation are conducted in order to investigate the strain localization behaviour of geomaterials under three-dimensional conditions. In the experiments, both normally consolidated and over-consolidated clay samples are tested with different strain rates. Using the distribution of shear strain obtained by an image analysis of digital photographs taken during deformation, the effects of the strain rates, the dilation, and the over-consolidation on strain localization are studied in detail. The analysis method used in the numerical simulation is a coupled fluid-structure finite element method. The method is based on the finite deformation theory, in which an elasto-viscoplastic model for water-saturated clay, which can consider structural changes, is adopted. The results of the simulation include not only the distribution of shear strain on the surfaces of the specimens, but also the distributions of strain, stress, and pore water pressure inside the specimens. Through a comparison of the experimental results and the simulation results, the mechanisms of strain localization are studied under three-dimensional conditions.